The Influence of Parenting Patterns on the Personal Social Development of Preschool Children - Ghozali, Sholahudin (University of Muhammadiyah Semarang, 2020)
The child's personal social development is greatly influenced by the environment and interactions between the child and the parents or other adults around them. The type of parenting style of parents towards their children will affect the attainment of the level of education, social skills and overall development of the child. The purpose of this study was to determine the effect of parenting style on the personal social development of preschool children. The method used in this research is descriptive correlation method and cross-sectional approach. The respondents of this study were 39 parents who have preschool children aged 3-5 years in Dukhan Qatar. Sampling was taken by total sampling. The results showed that the parenting style of preschoolers affected the personal social development of preschoolers (p = 0.028). It is recommended that parents of preschool-age children provide more encouragement to their children in terms of independence and socializing with the environment.